Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) for ovarian cancer in an Australian institution: lessons from 20 years’ experience - R. Farrell; W. S. Liauw; D. L. Morris (BMC Surgery, 2022)
Abstract Objectives We report the 20-year experience of the largest Australian unit performing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for ovarian cancer and reflect on learning opportunities. Methods A retrospective review of all cases of CRS for ovarian cancer at St George Peritonectomy Unit from Jan 1998 to Jan 2018 was performed. Prospectively collected data include age, stage, histology, disease extent (PCI), completeness of cytoreduction (CC score), HIPEC regime, 30-day surgical morbidity, disease recurrence, and death. Survival was computed using Kaplan–Meier method and analysed using log-rank tests and Cox-proportional hazards models. Results Forty-one women with advanced ovarian cancer (11 primary stage III/IV, 30 recurrent) underwent CRS, 29 (71%) with HIPEC. Most (68%) had high-volume disease (PCI > 15). In 98%, CC0/CC1 (residual < 2.5 mm) was achieved. Fourteen (34%) had grade 3/4 complications, 1 patient (2%) died within 30 days and 2 patients (5%) died within 90 days. Progression-free and median overall survival was 30.0 and 67.0 months for primary cancer, and 6.7 and 18.1 months for recurrent cancer. Survival was associated with platinum-sensitivity, PCI ≤ 15, and CC score 0, but not HIPEC. Conclusion This study reports outcomes for patients with advanced ovarian cancer patients treated in an Australian centre offering CRS and HIPEC. Whilst survival and morbidity outcomes were good for primary disease, they were poorer than predicted from the literature for cases of recurrent disease. The incorporation of evidence-based predictors of survival and multidisciplinary input are essential to achieve the best survival outcomes.